The Role of Supervisors and Principal in Increasing Teacher’s Competencies at Madrasah Aliyah Ma'arif NU Kencong Jember : - Wahib, Abd.; Asnawan, Asnawan (CV. Inara, 2021)
This paper talks about the roles of supervisors and principals of madrasah. The teachers as educators and mentors have an important influence in the world of education. The continuity of a good education cannot be separated from educational components such as professional administrator teachers, the control of supervisors, and school principals. The teacher competencies are pedagogic, personality, social, and professional competencies. The existences of supervisors are to providing guidance, coaching, and evaluation in all learning education units. It is an effort to improving the quality of the institution. Therefore, the principal as the highest leader in educational institutions automatically has responsibility for all that happens. In developing educational institutions, the principal has several important roles, namely, as an educator, manager, administrator, supervisor, leader, innovator, and motivator